Kierkegaard's Works of Love: From Benedict's Rule to More's Utopia - Joshua Neoh (Australian Journal of Law & Religion)
Thou shall love. But can love be commanded? That is one of the key questions that troubled Kierkegaard in the Works of Love. We learn from Saint Paul that ‘no human being will be justified … by works of the law’ (Romans 3:20), but what about the works of love? The law of love turns love into a duty. The worry about using the language of law to demand love is that it turns love from a free act to a commanded, and therefore compelled, act. The law of love is love bound by law. This paper examines how this puzzle about law and love is resolved in Kierkegaard’s Works of Love, Benedict’s Rule, and More’s Utopia.